Back to Basics: Counting Soft Surgical Goods. (26th February 2016) - Spruce, Lisa
Abstract: Retained surgical items (RSIs) pose serious consequences for patients and are a significant threat to patient safety. Perioperative team members are morally and ethically responsible for the prevention of RSIs and should understand how to reduce the risk of occurrence. The prevention of RSIs does not rest in the hands of one individual. It is a multidisciplinary endeavor that aims to reduce the risk of RSIs, and team members should hold each other accountable. This Back to Basics article focuses on the process of counting soft surgical goods, which are the most common RSIs.